Effects of Astragalus membranaceus Polysaccharides on Growth Performance, Physiological and Biochemical Parameters, and Expression of Genes Related to Lipid Metabolism of Spotted Sea Bass, Lateolabrax maculatus - Zhangfan Huang; Youling Ye; Anle Xu; Zhongbao Li (Aquaculture Nutrition)
This experiment investigated the effects of Astragalus membranaceus polysaccharides (AMP) on growth, physiological and biochemical parameters, and the expression of lipid metabolism-related genes in spotted sea bass, Lateolabrax maculatus. A total of 450 spotted sea bass (10.44±0.09 g) were divided into six groups and were given diets with different levels of AMP (0, 0.2, 0.4, 0.6, 0.8, and 1.0 g/kg) for 28 days, respectively. Results indicated that dietary intake of AMP significantly improved fish weight gain, specific growth rate, feed conversion, and trypsin activity. Meanwhile, fish fed with AMP manifested significantly higher serum total antioxidant capacity and activity of hepatic superoxide dismutase, catalase, and lysozyme. Lower triglyceride and total cholesterol were noted in fish fed with AMP (P<0.05). Moreover, hepatic ACC1 and ACC2 were downregulated by dietary intake of AMP, and PPAR-α, CPT1, and HSL were upregulated accordingly (P<0.05). Parameters with significant difference were analyzed by quadratic regression analysis, and results showed that 0.6881 g/kg of AMP is the optimal dosage for spotted sea bass in size (10.44±0.09 g). In conclusion, dietary intake of AMP can improve the growth, physiological status, and lipid metabolism of spotted sea bass, thereby indicating its promise as a potential dietary supplement.